IDNLearn.com provides a collaborative environment for finding accurate answers. Get the information you need from our experts, who provide reliable and detailed answers to all your questions.
Sagot :
5x∛69 = 6x√59
Subtract 6x√59 from each side:
5x∛69 - 6x√59 = 0
Factor the left side:
x (5∛69 - 6√59) = 0
Divide each side by (5∛69 - 6√59) :
x = 0
Subtract 6x√59 from each side:
5x∛69 - 6x√59 = 0
Factor the left side:
x (5∛69 - 6√59) = 0
Divide each side by (5∛69 - 6√59) :
x = 0
[tex]5x \sqrt[3]{69}=6x \sqrt{59}\ \ \ \Leftrightarrow\ \ \ 5x \sqrt[3]{69}-6x \sqrt{59}=0\\\\x(5 \sqrt[3]{69}-6 \sqrt{59})=0\ \ \ \Leftrightarrow\ \ \ x=0[/tex]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your questions deserve reliable answers. Thanks for visiting IDNLearn.com, and see you again soon for more helpful information.